Bimbingan dan Konseling - Wagiman Manik; Azizah; Indah Ansatu Nurani; Vella Afriani (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
Guidance and counseling are essential in education to support children’s emotional, psychological, social, and academic development. This research aims to explore the meaning of guidance and counseling, Islamic views on these practices, and the steps involved in their implementation. Using a qualitative method with a library study approach, the research gathers data from books, articles, and journals. The findings indicate that guidance is preventive, focusing on helping individuals understand and direct themselves optimally to prevent and prepare for problems. In contrast, counseling is corrective, involving intensive one-on-one sessions between the individual and counselor to address personal issues, with an emphasis on confidentiality, empathy, and care. Islam views counseling as a means to help individuals understand themselves and face challenges in line with Islamic values. Counselors are also tasked with guiding individuals to strengthen their relationship with Allah. Additionally, Islam highlights the importance of family and community support in the counseling process. The steps for implementing guidance and counseling include problem identification, diagnosis, and prognosis.